2003
DOI: 10.1080/0268396032000150799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Media Formats on Emotions and Impulse Buying Intent

Abstract: One way of generating revenue from broadband media content rests upon the assumption that multi-media content may trigger a greater intent to buy products and services impulsively. An experiment was performed in order to explore the effects of media formats on the emotions and impulse buying intentions for music compact discs (CDs). Three distinct media formats of World Wide Web pages were set up: (1) the text of the lyrics, (2) still images from the song's music video and (3) the music video itself. Each had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
194
2
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(215 citation statements)
references
References 31 publications
8
194
2
11
Order By: Relevance
“…Research has also noted that impulse buying is characterized by the impulsiveness with which a consumer acts. For example, Adelaar, Chang, Lancendorfer, Lee, & Morimoto (2003) confirmed that people who tend to be impulsive have a greater susceptibility to purchase items on impulse.…”
Section: Impulse and Contemplative Behavior: Impulsiveness Vs Need Fmentioning
confidence: 93%
See 1 more Smart Citation
“…Research has also noted that impulse buying is characterized by the impulsiveness with which a consumer acts. For example, Adelaar, Chang, Lancendorfer, Lee, & Morimoto (2003) confirmed that people who tend to be impulsive have a greater susceptibility to purchase items on impulse.…”
Section: Impulse and Contemplative Behavior: Impulsiveness Vs Need Fmentioning
confidence: 93%
“…Although impulse behavior is preceded by a consumer's intent to buy impetuously, environment cues such as the channel can enhance acting on impulse (Adelaar et al, 2003;Drossos, Kokkinaki, Giaglis, & Fouskas, 2014). The very nature of mobile devices can create in consumers an urge to buy impulsively.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Attention also could be measured through pupil dilation (Brasel and Gips 2008) and arousal by skin conductance (MacInnis, Moorman, and Jaworski 1991). Mood influences impulse shopping (Adelaar et al 2003), and by including measures of mood and automatic affective responses, such as facial EMG (Ravaja 2004), researchers may find that iTV ads alter brand evaluations through a pure affect-transfer process (e.g., Zajonc 1968; this effect is less likely for high-elaboration processing, Petty et al 1993).…”
Section: Limitations and Suggestions For Further Researchmentioning
confidence: 99%
“…Adelaar (2003) further notes on this dimension saying that, considering Stern's four categories of impulse buying, suggestion impulse buying is the relevant one in an on-line media environment since it enables consumers to seek additional information and eventually to buy items directly online or off-line. An on-line environment can provide an appropriate venue for acting upon the buying impulse.…”
Section: Categories Of Impulse Buyingmentioning
confidence: 99%